Exploring the influencing factor of urban industry development: An order parameter method - Dou, Zixin; Sun, Yanming; Wu, Beibei; Wu, Chuliang (Frontiers in Sustainable Cities, 2023)
This study aims to analyze the factor affecting the urban industry development in Guangzhou. Based on push-pull-mooring theory, we explain the reasons for choosing the above indicators and use order parameters to analyze their impact on the urban industrial development. The results show that: (1) Environment has an obvious promoting effect on the urban industrial development. This shows that the current environment and the urban industrial development have reached a balance. (2) Technology has a positive impact on the urban industrial development, but it needs to go through the technology running in period smoothly. (3) Different from other factors, finance has a crowding out effect on industrial development. However, the development of finance will promote the rapid development of industry in Guangzhou. (4) The impact of finance, technology and green on UID is applicable to different development stages of UID, that is, these variables are related. Lastly, we provided development suggestions for Guangzhou. This will lay a foundation for promoting its industry.